The Emerging Role of Estrogen Receptor-β in Human Reproduction - Su, Emily J.; Xin, Hong; Monsivais, Diana (Seminars in Reproductive Medicine, 2012)
Knowledge surrounding estrogen and estrogen receptor biology continues to evolve, and the diversity of their actions and complexity of their mechanisms are becoming increasingly evident. Estrogen receptor (ER) regulation of reproduction is no exception. Although it is well established that estrogen and ERα play key roles in mediating several reproductive biological processes, such as myometrial and endometrial growth, increasing evidence suggests that ERβ is also an important factor. ERβ is a key mediator in folliculogenesis and may also play a role in stimulating ovulation and regulating aspects of luteinization. ERβ is also expressed in higher quantities than ERα in the human myometrium and cervix during pregnancy, and thus it may play a part in the initiation of labor and parturition. Finally, ERβ is the sole ER expressed within the endothelium of the endometrium and the fetoplacental vasculature, and studies suggest that its role may contribute to angiogenic and vasomotor changes that play a role in both implantation and regulation of fetoplacental blood flow.
Keywords: estrogen receptor-β; isoforms; reproduction; pregnancy